TRANSLATION METHODS AND STRATEGIES IN THE CONTEXT OF SCIENCE FICTION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Science fiction is a complex and imaginative literary genre that presents unique challenges for translators. The presence of neologisms, scientific terminology, and culturally specific elements requires the use of specialized translation methods and strategies. This article examines the main translation methods such as literal translation, borrowing, adaptation, and calque, as well as strategies including handling neologisms, maintaining consistency, and applying domestication and foreignization. The study highlights the importance of balancing accuracy and creativity in order to produce effective translations of science fiction texts. The findings suggest that successful translation in this genre requires both linguistic competence and creative thinking.